Analisis teknoekonomi usaha pengolahan limbah cair organik menggunakan black soldier fly (Hermetia illucens) - Dwi Setiawan; Aditia Ginantaka; Miftahudin Miftahudin (AGROINTEK, 2022)
Liquid waste could not treated by primary treatment only, secondary or tertiary treatment is needed. However, this process has a high cost, so alternative processes are required. Black soldier fly (BSF) is an alternative treatment for a low-cost. In addition, waste treatment with BSF also produce animal food from the larvae produced and compost from processing residue. This processing product has a good economical value. However, a business project should be conducted a feasibility analysis to find out if the business is possible. Feasibility analysis is based on financial analysis of investment criteria: Net Present Value (NPV), Net Benefit Cost per ratio (Net B/C), Internal Rate of Return (IRR) and Payback Period (PP). The result is NPV Rp141,626142; Net B/C 1.15; IRR 17.6 % and PP 3.95 years. Based on that financial criteria, the organic waste processing into animal feed and fertilizers using BSF is possible. Sensitivity analysis shows that decreasing revenue over 8.04% could make this business unfeasible. The increasing of main material cost for almost 59% could keep this business feasible.